PERANAN INTELIJEN KEJAKSAAN DALAM PENGUNGKAPAN DUGAAN TINDAK PIDANA PENCUCIAN UANG DI WILAYAH HUKUM KEJAKSAAN TINGGI RIAU - Bintang Hari Setiawan; Erdianto '; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The crime of money laundering is an activity to conceal or disguise the origin of property which is the result of money laundering in various ways so that the wealth of the proceeds of the crime is difficult to be traced by law enforcement officers. In the case of handling the money laundering case itself in Indonesia can be handled by the Police of the Republic of Indonesia, the Corruption Eradication Commission, the Financial Services Authority, the Financial Transaction Reports and Analysis Center, and the Attorney General's Office.The type of research used in this study is empirical juridical or sociological research. The empirical juridical research is conducted by means of identifying the law and how the law's effectiveness is applicable in the society. While the nature of the research is descriptive which aims to provide a detailed and clear description of the role of intelligence prosecutor in the disclosure of alleged money laundering crime in the jurisdiction of the high prosecutor's office. While the population and the sample is the whole party related to the problems studied in this study. Sources of data used are primary, secondary and tertiary data sources, data collection techniques in this study with interviews and library studies.From the results of this study that the authors do can be concluded. First, Role of the Intelligence of the Riau High Prosecutor Office in the disclosure of alleged money laundering crime is to conduct activities and operations of judicial intelligence or investigation to collect data or information that can be used as evidence of whether or not a money laundering has occurred. The two obstacles faced by the Riau High Prosecutor's Intelligence namely the human resources factor, the factor of legislation that is perceived to be inconsistent with the demands of the development of society, the difficulty factor for the Intelligence Prosecutor's office in obtaining the evidence in the form of letters, valuable documents, or Related assets, lack of funding factors, lack of coordination by the Attorney General's Office with the relevant agencies, and the lack of planning factors undertaken by the Riau High Prosecutor's Intelligence. Third, Efforts made by Intelligence Attorney, should really pay attention to the principle of fairness and quality of human resources.Keywords: Money Laundering-Inquiry-Intelligence Prosecutor's Office